(untitled) (Journal of Computational Mathematics, 2022)
In this paper, matrix representations of the best spline quasi-interpolating operator over triangular sub-domains in S^1_2 (2206^(2)_mn), and coefficients of splines in terms of B-net are reviewed firstly. Moreover, by means of coefficients in terms of B-net, computation of bivariate numerical cubature over triangular sub-domains with respect to variables x and y is transferred into summation of coefficients of splines in terms of B-net. Thus concise bivariate cubature formulas are constructed over rectangular sub-domain. Furthermore, by means of module of continuity and max-norms, error estimates for cubature formulas are derived over both sub-domains and the domain.